What is known about the health and living conditions of the indigenous people of northern Scandinavia, the Sami? - Per Sjölander (Global Health Action, 2011)
The Sami are the indigenous ethnic population of northern Scandinavia. Their health condition is poorly known, although the knowledge has improved over the last decade.The aim was to review the current information on mortality, diseases, and risk factor exposure in the Swedish Sami population.Health-related research on Sami cohorts published in scientific journals and anthologies was used to compare the health condition among the Sami and the majority non-Sami population. When relevant, data from the Sami populations in Swedish were compared with corresponding data from Norwegian and Finnish Sami populations.Life expectancy and mortality patterns of the Sami are similar to those of the majority population. Small differences in incidences of cancer and cardiovascular diseases have been reported. The traditional Sami lifestyle seems to contain elements that reduce the risk to develop cancer and cardiovascular diseases, e.g. physical activity, diet rich in antioxidants and unsaturated fatty acids, and a strong cultural identity. Reindeer herding is an important cultural activity among the Sami and is associated with high risks for accidents. Pain in the lower back, neck, shoulders, elbows, and hands are frequent among both men and women in reindeer-herding families. For men, these symptoms are related to high exposure to terrain vehicles, particularly snowmobile, whereas for women psychosocial risk factors seem to more important, e.g. poor social support, high effort, low reward, and high economical responsibilities.Although the health condition of the Sami population appears to be rather similar to that of the general Swedish population, a number of specific health problems have been identified, especially among the reindeer-herding Sami. Most of these problems have their origin in marginalization and poor knowledge of the reindeer husbandry and the Sami culture in the majority population. It is suggested that the most sustainable measure to improve the health among the reindeer-herding Sami would be to improve the conditions of the reindeer husbandry and the Sami culture.